THE DISTRIBUTION OF BUILDINGS AT VARIOUS FLOOD HAZARD LEVELS IN KEBON BARU VILLAGE, TEBETSUB-DISTRICT, SOUTH JAKARTA - Wardana, Muhammad Wahyu; Setiawan, Cahyadi; A'Rachman, Fauzi Ramadhoan (Universitas Negeri Surabaya, 2023)
Floods have the potential to threaten human life and destroy property including buildings. Kebon Baru Village is one of the villages that often experiences floods. This research focuses on the Level of Flood Hazard in Kebon Baru Village. The method used is descriptive quantitative with overlay analysis techniques. The parameters used are altitude, distance from the river, land use, and buildings. Based on the results, Kebon Baru Village has three levels of flood hazard, namely low, moderate and high. Low level has 4564 buildings, moderate level has 1060 building and high level has 405 buildings. The level of flood hazard found in Kebon Baru Village is more influenced by the height and distance from Ci Liwung. The lower altitude and the closer to Ci Liwung, the higher of flood hazard level, on the contrary, the higher altitude and the farther distance, the lower flood hazard level. Keywords : Buildings Distribution, Flood Hazard Level, Kebon Baru Village